A Soft Skin Adhesive (SSA) Patch for Extended Release of Pirfenidone in Burn Wounds - Eugene P. Chung; Jesse Q. Nguyen; Tobias Tellkamp-Schehr; Katja Goebel; Anita Ollek; Cliff Krein; Adrienne R. Wells; Eliza A. Sebastian; Anja Goebel; Svenja Niese; Kai P. Leung (MDPI AG, 2023)
As much as half or more of deep partial-thickness burn wounds develop hypertrophic scarring and contracture. Once formed, treatments are only minimally effective. Pirfenidone (Pf), indicated for treatment of idiopathic pulmonary fibrosis, is an anti-inflammatory and anti-fibrotic small molecule that potentially can be repurposed as a preventative against scarring in burn wounds. We present a drug-in-matrix patch with a soft skin adhesive (SSA) wound-contacting layer for multi-day drug delivery of Pf into burn wounds at the point of injury. Our patch construction consists of an SSA adhesive layer (Liveo™ MG7-9850, Dupont, Wilmington, DE, USA) for wound fixation, an acrylic co-polymer drug matrix (DURO-TAK 87-2852, Henkel, Düsseldorf, Germany) as the drug (Pf) reservoir, and an outermost protective polyurethane backing. By employing a drug-in-matrix patch design, Pf can be loaded as high as 2 mg/cm2. Compared to the acrylic co-polymer adhesive patch preparations and commercial films, adding an SSA layer markedly reduces skin stripping observed under scanning electron microscopy (SEM). Moreover, the addition of varying SSA thicknesses did not interfere with the in vitro release kinetics or drug permeation in ex vivo porcine skin. The Pf patch can be easily applied onto and removed from deep partial-thickness burn wounds on Duroc pigs. Continuous multi-day dosing of Pf by the patches (>200 μg/cm2/day) reduced proinflammatory biomarkers in porcine burn wounds. Pf patches produced by the manual laboratory-scale process showed excellent stability, maintaining intact physical patch properties and in vitro biological activity for up to one year under long-term (25 °C at 60% RH) and 6 months under accelerated (40 °C at 75% RH) test conditions. To manufacture our wound safe-and-extended-release patch, we present scale-up processes using a machine-driven automated roll-to-roll pilot scale coater.